Analysis of Web-Based Geographic Information System Mapping of Broken Roads in Kampar Regency - Dilla fafira; Novi Yona Sidratul Munti; Beni Setiawan (Journal of Engineering Science and Technology Management, 2021)
Road is a very vital land transportation infrastructure and transportation route. Apart from being transportation, roads also function as a medium of socialization and accessibility for the community. Damage to the road is a big problem for some people who use the road every day. Therefore, a public complaint system is needed to the authorities in reporting the location of damaged roads, so that road repairs can be carried out quickly. The purpose of this study is to make it easier for the public to report damaged road conditions using a damaged road reporting system website that can be accessed online. The research method used in this study is the waterfall method. This waterfall method has a sequential flow of software starting from planning, analysis, design, implementation, testing and maintenance. The design of this system uses Unified Modeling Language (UML) and Object Oriented Analysis Design (OOAD). The programming language used is PHP Framework Yii and MySQL database. This research was conducted on a website reporting damaged roads in Kampar Regency which also provides information on roads that have been repaired in Kampar Regency and provides information related to the Kampar PUPR Service. With this system, PUPR's performance in repairing damaged roads that have been reported by the general public will be better.